2012
DOI: 10.5539/ies.v5n3p67
|View full text |Cite
|
Sign up to set email alerts
|

Senior Secondary School Science Teachers in Delta and Edo States Conceptualization about the Nature of Science

Abstract: The major purpose of this study was to find out the conceptions of science teachers about the nature of science. To guide this study, four research questions were asked and four hypotheses tested. The design of the study was descriptive survey and instrument used for data collection was a 22 item questionnaire. The sample of the study consisted of 400 science teachers drawn from senior secondary schools in Edo and Delta states. The data collected were analyzed with simple percentages and Chi square statistics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…That is if teachers receive training through the same curricula, same instructors, or similar processes, their NOS conceptions invariably remain the same or similar irrespective of their gender (Adedoyin & Bello, 2017; Saif, 2016 ). As per Ajaja ( 2012 ), both male and female science teachers would have the highest instances to see the NOS from a similar lens if they handle the same curriculum in their daily classroom teaching, including textbooks. On the other hand, Dogan and Abd-El-Khalick ( 2008 ) espouse reasons from different and bigger lines of thought.…”
Section: Review Of Literaturementioning
confidence: 87%
See 1 more Smart Citation
“…That is if teachers receive training through the same curricula, same instructors, or similar processes, their NOS conceptions invariably remain the same or similar irrespective of their gender (Adedoyin & Bello, 2017; Saif, 2016 ). As per Ajaja ( 2012 ), both male and female science teachers would have the highest instances to see the NOS from a similar lens if they handle the same curriculum in their daily classroom teaching, including textbooks. On the other hand, Dogan and Abd-El-Khalick ( 2008 ) espouse reasons from different and bigger lines of thought.…”
Section: Review Of Literaturementioning
confidence: 87%
“…A few studies report that there is no significant relationship between science teachers’ gender and their conceptions of the NOS (Saif, 2016 ; Oluwatayo, 2011 ; Taale, 2014 ; Yaman & Nugoglu, 2010). For instance, the descriptive survey carried out by Adedoyin and Bello (2017) and Ajaja ( 2012 ) Nigeria revealed an equal proportion of male and female secondary science teachers with a traditionalist and/or constructivist view of the NOS. In their study of the 201 Turkish science teachers, Yaman and Nugoglu ( 2010 ) also found out that the conceptions of the NOS held by male science teachers are statistically not significant from the conceptions of the NOS held by female science teachers.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A literatura tem indicado a presença de concepções inadequadas sobre a ciência nos diversos níveis de formação (p. ex., Abd-El-Khalick & Ajaja, 2012;Hacieminoglu, Yilmaz-Tuzun, & Ertepinar, 2012;Moss, Abrams & Robb, 2001;Waters-Adams & Nias, 2003), enunciando a necessidade de entender os fatores que levam a tais concepções, de refletir sobre o conhecimento que vem sendo construído na área e de repensar estratégias que sejam eficazes para superar concepções pouco informadas acerca da ciência.…”
Section: Introductionunclassified
“…Aikenhead, 1973;Lederman & O'malley, 1990, Lederman, 1992Harres, 1999;Abd-El-Khalick & Lederman, 2000). Os trabalhos sobre concepções de NdC de professores em formação ou em exercício, também não têm sido otimistas quanto à aproximação das concepções de docentes de uma visão considerada bem informada (Waters-Adams & Nias, 2003;Ajaja, 2012;Hacieminoglo et al, 2012).…”
Section: Introductionunclassified